Peran Guru dalam Menumbuhkan Motivasi Belajar Siswa pada Mata Pelajaran IPS Kelas V di UPT SD Negeri 31 Gresik - Muis Faiyah; Ismail Marzuki (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The Role of the Teacher in Growing Student Learning Motivation in Social Studies Subjects Class V at UPT SD Negeri 31 Gresik. (Supervised by Ismail Marzuki, M.Pd and Iqnatia Alfiansyah, M.Pd). This study aims to find out how the role of the teacher and the teacher's constraints in fostering student learning motivation in social studies class V at UPT SD Negeri 31 Gresik. The type of research used is qualitative research. The data collection techniques used in this study were interviews, observation, and documentation of research subjects so as to provide a clear picture of the teacher's role and the teacher's constraints in fostering student motivation in social studies class V at UPT SD Negeri 31 Gresik. The results of the study show that the teacher's role in fostering student learning motivation is the teacher as evaluator, the teacher gives gifts, gives additional value, praise. The teacher as class manager, the teacher pays attention to the concentration of students by going around and rolling student seats. The teacher as a facilitator and mediator, the teacher provides the facilities that have been provided by the school and for media the teacher prepares media from home according to the material to be taught. The teacher as a demonstrator, the teacher provides a method that is adapted to the learning material to be taught and the teacher also uses language that is easily understood by students. The teacher's constraints are due to external factors such as the environment and family as well as internal factors such as student interest in learning and the level of understanding of each student is different.